Massive gastrointestinal bleeding after chemotherapy for gastric lymphoma - Sousa, M (2016)
INTRODUCTION: Gastrosplenic fistula (GSF) is a rare condition almost always associated with lymphoma, with gastric and splenic involvement. CASE REPORT: We report a 52 year old male with gastric lymphoma admitted to the emergency department with hematemesis. The first chemotherapy cycle had been completed four weeks before. Oesophagoduodenoscopy showed a pulsatile ulcerated lesion. Surgical hemostasis was performed. Four days after surgery, the patient initiated sudden and massive upper gastrointestinal bleeding with hemodynamic compromise. A gastrosplenic fistula was recognized during emergency laparotomy and an en bloc total gastrectomy and splenopancreatectomy resection was performed, with massive blood transfusion. Patient was discharged 13 days after the second surgery. DISCUSSION: Gastrosplenic fistula is a rare condition, previously described associated with gastric lymphoma at presentation or after treatment. A prompt recognition of the underlying pathology could avoid a second surgery. CONCLUSION: A systematic and interdisciplinary approach is the key for success in rare challenging emergencies. Infrequent etiologies must always be considered as they need specific therapeutic approaches that defy paradigms.